Preparation of non-woven nanofiber webs for detoxification of nerve gases. (28th September 2019) - Lee, Jaemin; Seo, Eunbyeol; Yoo, Mi; Kim, Sohee; Choi, Jihyun; Jung, Hyunsook; Lee, Hae Wan; Lee, Hyuck Mo; Kim, Hyun You; Lee, Bumjae; Lee, Kyung Jin
Abstract: Non-woven nanofiber web with high surface areas and abundant functional groups were fabricated through electrospinning and chemical vapor deposition (CVD) in order to develop functional non-woven nanofiber webs for detoxifying simulant of chemical warfare agents. Functional groups that can hydrolysis diisopropyl fluorophosphate (simulant of G-series agents) were selectively modified onto the electrospun PAN nanofibers without causing deterioration of the fiber morphology. In order to achieve the most suitable conditions for functionalization, the CVD reaction temperature was adjusted and various functional groups were introduced. Here, CVD of ethylene diamine at 120 °C of reaction temperature shows the best detoxifying efficiency against diisopropyl fluorophosphates (DFP), which is simulant of G-series chemical warfare agent (complete removal of DFP within 24 h under humid condition). Density functional theory (DFT) calculations clarified the optimized functional groups for effectively detoxifying nerve gas agent (G types). Both of simulation and experimental results prove that the co-existence of hydroxyl and amine groups will be beneficial in detoxifying reaction (over 80% decomposition within 4 h). Graphical abstract: Self-detoxifying functional non-woven nanofiber web with high catalytic activity were prepared by combined process of electrospinning and chemical vapor deposition.Image 1 Highlights: Self-detoxifying non-woven nanofiber web with high catalytic activity are prepared. Catalytic functional groups can be introduced via chemical vapor deposition. Catalytic non-woven nanofiber web shows enhanced detoxifying ability. DFT calculations confirmed enhanced ability for catalytic reaction. Co-existence of amine and hydroxyl groups will be helpful for catalytic reaction.